Stethoscopes: a potential source of hospital acquired infection - Venkatesan, Kalpana Devi; Chander, Senthil; Victor, Kalavathy (International Journal of Advances in Medicine, 2019)
Background: Nosocomial infection has been recognized for over a century as both a critical problem affecting the quality of health care and a leading cause of morbidity, mortality and increased health care cost. Stethoscopes because of their universal use by medical professional, can be a potential source of nosocomial infections. The study was conducted to determine the bacterial contamination of stethoscopes used by health care staff as well as the practices used for cleaning them. Methods: A structured questionnaire was administered to health workers and the surface of the diaphragm of their stethoscopes swabbed for bacteriological analysis using standard techniques. Results: Of the 65 stethoscopes sampled, 33(50.8%) showed bacterial growth. All the bacterial isolates were found to be gram positive organism. The isolates were Micrococcus spp. (35.8%), Coagulase negative staphylococcus (CONS) (30.8%), Bacillus spp. (15.4%), Staphylococcus aureus (10.3%) and Diphtheroids (7.7%). Conclusions: Further research is needed to solve the question whether stethoscope contamination actually results in infection in the patient. However strict adherence to disinfection practices by health workers can minimize cross-contamination and ensure patient safety in hospital environments.